Game-based learning as students' learning strategies in enhancing problem-solving skills - Amran, Aryanti; Ab. Jalil, Habibah; Sulaiman, Tajularipin (Faculty of Educational Studies, Universiti Putra Malaysia, 2019)
In line with the components in the 4.0 Industrial Revolution Framework, the Ministry of Education introduced an action plan that is leveraging ICT for learning. With the use of ICT-based education technology, the Ministry strongly emphasises on producing highly thinking skilled students in problem-solving. Game-based learning has been recognized as a potential approach to elevate thinking skills in problem solving. This teaching method is notable to be best applied in student-centered learning environment. Several studies have been conducted in scrutinising the increase in problem-solving in game-based learning. However, there has been no study conducted that measure the level of problem-solving skills in game-based learning through different formal learning strategies. Therefore, this paper aims to discuss the studies on students' problem-solving skills in game-based learning through individual or collaborative learning strategies.